DATA PROCESSING SYSTEM HEART SURGERY PATIENTS CIPTO MANGUNKUSUMO HOSPITAL - Bambang Sevianus; Hariyanto, SKom, MMSI Hariyanto, SKom, MMSI (Jurnal Sistem Informasi, 2003)
And the process of recording patient data on the previous system, namely the processof recording patient data manually as well as many feel the problem for CardiacSurgery. Therefore, the Cardiac Surgery implement computerized patient dataprocessing system which is expected to assist and facilitate the activity so that patientdata recording and processing data.Patient data processing system of Cardiac Surgery inpatient unit can yieldinformation about a patient's life history, namely that contains data about themselvesand the statements of operations from the patient.The system that the authors of this draft would be able to assist in handling the job,especially in data processing for the patient.